Applying Lithium-Ion Second Life Batteries for Off-Grid Solar Powered System—A~Socio-Economic Case Study for Rural Development - Joern Falk; Antonio Nedjalkov; Martin Angelmahr; Wolfgang Schade (Zeitschrift für Energiewirtschaft, 2020)
Socio-economic development in the rural regions of Africa cannot succeed without suitable infrastructure. An essential key to this is electrification. Despite various national and international activities and expansion programmes, and a~wide variety of actors, their implementation is progressing slowly. In order to supply remote areas with electricity, off-grid system technologies have become increasingly common in recent years. In this article, we present the use of a~photovoltaic system in conjunction with a~85 kWh second life lithium-ion battery (LIB) as an off-grid hybrid system to electrify an island in Lake Victoria in Tanzania as a~socio-economic case study.This off-grid hybrid system was able to supply an average of 42.31 kWh of energy per day, with the daily demand of the key infrastructure successfully connected in the project, such as the local hospital and school, amounting to 18.75 kWh. The scaled annual production of 15,443.16 kWh offers enough potential to include private households as well as the local fishing industry in the power supply. Assuming an expected lifetime of 15~years, the described system amortises itself from the 4th~year. In addition, this project should also serve as a~possible second life scenario for batteries with regard to the rapidly developing global electromobility and the perspective return of used LIBs. An economic and an ecological evaluation shows a~solution approach of using a~second life lithium-ion battery compared to a~conventional diesel generator solution. The consideration of health aspects is included in the evaluation.
Keywords: 620; Off-grid; Mini-grid PV; Second life of lithium-ion battery (LIB); Sustainable energy; Circular economy; Techno-socio-economic aspects assessment; Energy in developing countries; Power generator replacement; Power solution for rural areas in sub-Saharan Africa